Assessing the Alignment Between School Leadership Marketing Mix Strategies and Parental Perceptions: A 7 Ps Analysis of Private Schools in Dubai – Case Study - ABU LUGHOD, RAWAN (2025)
In Dubai’s competitive environment, private schools must implement effective marketing strategies to attract and retain students. Using the 7 Ps marketing mix framework (Product, Price, Place, Promotion, People, Process and Physical Evidence), this study will investigate the alignment between marketing strategies implemented by school leaders and parents’ expectations. Using a mixed-methods approach, qualitative interviews with school marketing officials in addition to parent quantitative surveys were included. Results show that while school leaders’ main marketing tool is digital marketing and brand reputation, parents give teacher quality, curriculum relevance and safe environment top importance. The research emphasises the importance of a comprehensive and holistic marketing plan combining institutional goals with family expectations. Suggestions call for better extracurricular activities, matching promotional initiatives with parental tastes and raising instructor credentials. The results contribute to the body of knowledge on school marketing and offer practical advice for learning environments trying to improve their market orientation.